Biotic drivers of river and floodplain geomorphology – New molecular methods for assessing present‐day and past biota. Issue 1 (8th November 2017) - Larsen, Annegret; Alvarez, Nadir; Sperisen, Christoph; Lane, Stuart N.
Abstract: Geomorphology has increasingly considered the role of biotic factors as controls upon geomorphic processes across a wide range of spatial and temporal scales. Where timescales are long (centennial and longer), it has been possible to quantify relationships between geomorphic processes and vegetation using, for example, the pollen record. However, where the biotic agents are fauna, longer term reconstruction of the impacts of biological activity upon geomorphic processes is more challenging. Here, we review the prospect of using environmental DNA as a molecular proxy to decipher the presence and nature of faunal influences on geomorphic processes in both present and ancient deposits. When used appropriately, this method has the potential to improve our understanding of biotic drivers of geomorphic processes, notably fauna, over long timescales and so to reconstruct how such drivers might explain the landscape as we see it today. Copyright © 2017 John Wiley & Sons, Ltd.